1984
DOI: 10.1159/000469450
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Congenital Hyperammonemias

Abstract: A rapid recognition of congenital hyperammonemia, a clear diagnostic workup and institution of a combined treatment without delay, by restriction of nitrogen supply, adequate caloric supply, substitution of missing metabolites, and use of alternate routes of nitrogen excretion will help to control hyperammonemic crises and improve the prognosis. For long-term treatment the use of essential amino acid mixtures and perhaps of antiserotoninergic agents is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In most of these cases, hyperammonemia develops in the neonatal period and clinical features include feeding refusal, vomiting, abnormal muscle tone, lethargy, seizures and coma leading to death within a few days. Recommended guidelines for the initial medical management include protein avoidance, adequate caloric support, supply of arginine and carnitine, and pharmacological priming of alternative pathways for nitrogen excretion [3,4,5]. Poor response to pharmacological therapy requires prompt exogenous removal of toxic compounds to prevent permanent brain damage or death.…”
Section: Introductionmentioning
confidence: 99%
“…In most of these cases, hyperammonemia develops in the neonatal period and clinical features include feeding refusal, vomiting, abnormal muscle tone, lethargy, seizures and coma leading to death within a few days. Recommended guidelines for the initial medical management include protein avoidance, adequate caloric support, supply of arginine and carnitine, and pharmacological priming of alternative pathways for nitrogen excretion [3,4,5]. Poor response to pharmacological therapy requires prompt exogenous removal of toxic compounds to prevent permanent brain damage or death.…”
Section: Introductionmentioning
confidence: 99%
“…In E.coli K12, the genes involved in methionine biosynthesis are scattered throughout the chromosome (1). Genetic evidence suggested that the expression of all the met genes is subject to a common negative regulatory mechanism (2,3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Mean values reported vary between 46% (Green et al, 1983) and 74% (Letarte et aI., 1985). This is in contrast to the reasonable expectation (Bachmann, 1984) that slightly more than the ingested dose of benzoate should be excreted because of the endogenous production of hippurate, which is approximately 0.14 mmolper day in controls and 0.31 mmol per day in hyperammonaemic infants (Green et al, 1983). It has been postulated that the incomplete conversion of ingested benzoate to hippurate is a result of decreased availability of glycine (Simkin and White, 1957).…”
mentioning
confidence: 73%